The Effectiveness of Rewards And Incentives In Increasing The Performance of Retail Employees In Pamekasan Regency - Khas, As'adi; Hidayat, Rachmad; Alvin Arifin (Nusantara Journal of Multidisciplinary Science, 2024)
The objective of this research is to determine the impact of incentives and remuneration on the performance of employees in retail enterprises located in Pamekasan Regency. The research utilises quantitative methodologies such as surveys and multiple linear regression analysis. The research used a population of 364 retail workers in Pamekasan Regency and selected a sample of 191 employees using the Slovin algorithm. The research findings suggest that partial incentives have a beneficial and substantial impact on performance. Incentives have a favourable and substantial impact on performance. Additionally, this research discovered that incentives and remuneration had a substantial impact on employee performance. The findings of this research have practical relevance for retail firm management in formulating incentive and pay strategies to enhance employee performance.